Islamic Banking in the Philippines: Financial Performance During the Covid-19 Pandemic - Sali, Najeeb Razul (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study investigates the impact of the Covid-19 pandemic on the financial performance of the Al-Amanah Islamic Investment Bank of the Philippines (AAIIBP), the country’s first and only Islamic bank. The research focuses on several key financial indicators, including Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), and the performance of both Islamic and conventional deposits. Using quarterly data from the first quarter of 2019 to the fourth quarter of 2020, this study applies a significant difference test to compare the financial performance before and during the pandemic. The findings reveal that while the total assets and conventional deposits of the bank decreased during the pandemic, Islamic deposits saw a significant increase. Additionally, the Return on Deposits (ROD) and net income showed positive growth, while the CAR experienced a significant decline. These results suggest that, despite the global economic crisis, AAIIBP demonstrated resilience, particularly in its Islamic banking operations. The study provides insights into the unique stability of Islamic banks in a non-Muslim country during economic turmoil, offering valuable information for policymakers and financial institutions in strengthening Islamic banking practices.